Petrology of the Fort Smith - Great Slave Lake radiometric high near Pilot Lake, N.W.T. - Burwash, R. A.; Cape, D. F. (Canadian Journal of Earth Sciences, 1981)
Near Pilot Lake, the east boundary of the Fort Smith – Great Slave Lake radiometric high coincides with the contact of a well-foliated, porphyroblastic microcline–plagioclase–quartz-garnet–biotite gneiss 1 (Pilot Lake Gneiss) with a hybrid assemblage of quartzite, mica schist, garnet–cordierite gneiss, and minor amphibolite (Variable Paragneiss). Anomalously high concentrations of uranium and thorium are associated with mafic-rich, lenticular bodies with a mineral assemblage biotite + monazite + zircon + ilmenite + hematite ± apatite ± plagioclase ± quartz. The mafic pods occur within both the Variable Paragneiss and the Pilot Lake Gneiss. Corundum and spinel occur in the mafic lenses and sillimanite, kyanite, and hypersthene in other inclusions in the Pilot Lake Gneiss.The ilmenite–magnetite–monazite–zircon–apatite assemblage is interpreted as a "black sand" concentration in a clastic sedimentary sequence subsequently metamorphosed by a regional granulite facies event. A granitic pluton intruded during the same orogenic cycle assimilated the clastic metasedimentary rocks containing black sand interlayers, becoming enriched in thorium from the monazite. A second metamorphic event at lower P–T conditions, accompanied by strong cataclasis, developed the texture of the Pilot Lake Gneiss as now observed. Shearing within the gneiss locally concentrated hematite + quartz + uranium.Regional tectonic extrapolations suggest that the pyroxene granulite event was Kenoran and the later amphibolite event Hudsonian.